Risk factor screening for gestational diabetes mellitus based on the 2013 WHO criteria. Issue 6 (June 2019) - Benhalima, Katrien; Van Crombrugge, Paul; Moyson, Carolien; Verhaeghe, Johan; Vandeginste, Sofie; Verlaenen, Hilde; Vercammen, Chris; Maes, Toon; Dufraimont, Els; De Block, Christophe; Jacquemyn, Yves; Mekahli, Farah; et al.
Abstract : Objective: Since many European countries use risk factor screening for gestational diabetes mellitus (GDM), we aimed to determine the performance of selective screening for GDM based on the 2013 WHO criteria. Design and methods: Overall, 1811 women received universal screening with a 75 g oral glucose tolerance test (OGTT) with GDM in 12.5% ( n = 231) women based on the 2013 WHO criteria. We retrospectively applied different European selective screening guidelines to this cohort and evaluated the performance of different clinical risk factors to screen for GDM. Results: By retrospectively applying the English, Irish, French and Dutch guidelines for selective screening, respectively 28.5% ( n = 526), 49.7% ( n = 916), 48.5% ( n = 894) and 50.7% ( n = 935) had at least one risk factor, with GDM prevalence of respectively 6.5% ( n = 120), 7.9% ( n = 146), 8.0% ( n = 147) and 8.4% ( n = 154). Using maternal age ≥30 and/or BMI ≥25 for screening, positive rate was 69.9% ( n = 1288), GDM prevalence 10.2% ( n = 188), sensitivity 81.4% (CI: 75.8–86.2%) and specificity 31.8% (CI: 29.5–34.1%). Adding other clinical risk factors did not improve detection. GDM women without risk factors had more neonatal hypoglycemia (14.4 vs 4.0%, P = 0.001) and labor inductions (39.7 vs 25.9%, P = 0.020) than normal-glucose tolerant women, and less cesarean sections than GDM women with risk factors (13.8 vs 31.0%, P = 0.010). Conclusions: By applying selective screening by European guidelines, about 50% of women would need an OGTT with the lowest number of missed cases (33%) by the Dutch guidelines. Screening with age ≥30 years and/or BMI ≥25, reduced the number of missed cases to 18.6% but 70% would need an OGTT.